The carbon effects of the evolution of node status in the world trade network - Zhang, Xiaoling; Tang, Decai; Kong, Shanyou; Wang, Xiuli; Xu, Tong; Boamah, Valentina (Frontiers in Environmental Science, 2022)
Trade promotes economic development and contributes to closer ties between countries or regions of the world, but it also has a great impact on the global environment, especially in terms of CO2 emissions. This paper analyzes the structural characteristics of the trade relations networks of major countries or regions in the world based on a complex network approach. The results show that trade relations among countries are relatively stable from 2000 to 2020, trade links between members of regional integration organizations are increasing, the top ten countries in terms of importance are mainly developed countries, and China has very close trade relations with most countries. Based on the analysis of structural characteristics, the impact of changes in each country's network status on its carbon emissions is analyzed, using indicators such as degree centrality of each node as independent variables and their domestic carbon emission levels as dependent variables. A significant positive effect of in-degree centrality was found in developed countries, with no significant effect of out-degree centrality, while a positive effect of in-degree centrality was found in developing countries. The negative effect of betweenness centrality on carbon emissions is significant, but the opposite effect is found for eigenvector centrality, with no effect of closeness centrality on carbon emissions.